Developments in fluorocyclization methodologies. - Wilkinson, S; Salmon, R; Gouverneur, V (2009)
Fluorinated organic compounds constitute a significant proportion of medicines marketed today. Since heterocycles are submotifs frequently encountered in lead compounds, the corresponding fluorinated molecules that possess coupling functional groups to increase structural complexity are sought-after building blocks, especially those with stereogenic elements. To access fluoro-heterocycles, fluorocyclizations constitute an important category of reactions that permit multiple bond construction in one pot. Reactions featuring both nucleophilic and electrophilic sources of fluorine have proved valuable for the delivery of fluorinated carbo- and heterocycles. Mechanistically, two scenarios have been validated with the fluorination occurring either prior to or after the cyclization event. Fluorinated biologically active molecules prepared by employing a fluorocyclization protocol are rare, with two notable exceptions being the synthesis of fluorogypsetin and fluorobrevianamide E. Various levels of diastereocontrol were obtained with best results observed when the cyclization step precedes the fluorination. To date, asymmetric fluorocyclizations have not been explored, with the exception of a Nazarov fluorination process. In essence, this process features a catalytic asymmetric cyclization followed by a diastereoselective fluorination. Asymmetric fluoroheterocyclizations are, however, not known. For this methodology to serve medicinal chemistry, conceptual advances are essential to access fluorinated pharmacophores with programmable stereocontrol as and when necessary.